Neoliberalism in Argentina and Chile: common antecedents, divergent paths - Undurraga, Tomás (Revista de Sociologia e Política, 2015)
This paper contrasts the experiences of neoliberalism in Argentina and Chile, exploring why two countries that implemented apparently similar market reforms came to different stances on marketization: a post-neoliberal politics in Argentina, and a tempered neoliberalism in Chile that has only recently come under scrutiny. The paper traces the common antecedents that inspired these reforms and the different outcomes and reactions that they produced. In contrast to recent literature, which emphasizes one or another explanatory factor, this article offers a synthetic comparison of the historical, political, economic, and ideological factors in play, helping to understand how capitalists achieved a hegemonic class position in Chile and not in Argentina.